Vivos los llevaron, vivos los queremos: estratégias e conflitos na transmissão da experiência em um contexto de violência política - Verônica Gomes Olegário Leite (2020)
This thesis presents an analytical study about the relationship between art and testimony. The corpus used comes from the Ayacucho region, in the Peruvian Andes, and is beheld on the analysis of narrative presentations of traumatic memory made through drawings and paintings for the Rescate por la Memória Competition, organized by the Yuyarisun Collective in 2004, from the Internal Armed Conflict lived in this region between 1980-2000. The conduct of the research is justified by its theoretical relevance, in the area of Modern and Contemporary Literatures and by the low occurrence of analytical studies on the relations of imagery representation of the memory of violence from a Latin American perspective. It is supported the hypothesis that the reception of the narratives of this memory is subject by criteria of recognition or denial of the political existence of those who produce them.Based on dialogues between the researcher and leaders of the Asociación Nacional de Familiares de Secuestrados, Detenidos y Desaparecida del Perú - ANFASEP in Ayacucho, during the research immersions, it was possible to identify strategies for the construction and dissemination of local witness narratives about the violence experienced. Such presentations are different from those produced in the capital of the country, which have greater visibility and are consequently more easily incorporated into the official memory of the nation, but which, at the same time, distance themselves from the first person productions carried out at the geographical center of violence. The study will use two methodological strategies: the first is based on a theoretical reflection about social relations that leads to the possibility of recognizing or not the political existence of a subject, connected to the historical political analysis of the Ayacucho region. The second strategy will be the critical imaginary narratives analysis of the traumatic memory made by the residents of Ayacucho for the already reported Contest.